Oral History and the War : The Nazi Concentration Camp Experience in a Biographical-Narrative Perspective - Filipkowski, Piotr 1977- (Studies in Contemporary History, 2019)
This book is rooted in the author’s experience as an interviewer and researcher in the Mauthausen Survivors Documentation Project – the biggest European oral history project devoted to a single Nazi concentration camp system, realized in the years 2002/2003 at the University of Vienna. Over 850 Mauthausen survivors have been recorded worldwide, more than 160 of them in Poland, and over 30 by the author. The work offers an in-depth analysis of Polish survivors’ accounts, sensitive to both, form and content of these stories, as well as their social and cultural framing. The analysis is accompanied by an interpretation of (Polish) camp experiences in a broader biographical and historical perspective. The book is an interpretive journey from camp experiences, through the survivors’ memories, to narratives recalling them − and backwards